Effects of Health Intentions and Health-promoting Behavior on Selfesteem among School-aged Children in South Korea - Kim, Jin; Jeon, Ga E.; Cha, Nam Hyun (Current Pediatric Reviews, 2023)
Background: The purpose of this study was to identify the predictors of self-esteem and the relationships between health-promoting behavior, health intentions, and self-esteem among school-aged children and provide basic data for the development of programs that can influence self-esteem among school-aged children in South Korea. Introduction: This study aimed to identify the predictors of self-esteem and the relationships between health intentions and health-promoting behavior and self-esteem among school-aged children. Methods: The study design was a cross-sectional study. The data were collected using a selfreported questionnaire on health intentions, health-promoting behavior, and self-esteem. The data were collected from elementary school students from February 3 to 13, 2020. Data analysis was performed using the SPSS program. Results: Positive correlations were found between self-esteem and both health-promoting behavior (r=.503, p < 0.001) and health intentions (r=.511, p < 0.001). Also, the relationship between health intentions and health-promoting behavior (r = 0.629, p < 0.001) exhibited positive correlation. Selfesteem was identified as a significant predictor of health intentions (β = 0.28, p < 0.001), healthpromoting behavior (β = 0.21, p < 0.001), school records (β = -0.20, p < 0.001), perceived health status (β = 0.18, p < 0.001), and academic grade (β = -0.10, p < 0.05), with an explanatory power of 39.0%. Conclusion: The results indicated that self-esteem positively affects health intentions and healthpromoting behavior.
Keywords: health intention